2007
DOI: 10.1080/13693780701625131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of virulence of differentSporothrix schenckiiclinical isolates using experimental murine model

Abstract: The virulence of two strains of Sporothrix schenckii isolated from patients with lymphocutaneous or disseminated sporotrichosis were examined in BALB/c mice (Group 1 and 2, respectively). The mice were inoculated subcutaneously into the left hind footpad with 4 x 10(6) S. schenckii yeast cells in order to evaluate (i) the development of cutaneous lesions, (ii) signs of inactivity, (iii) weight loss, (iv) survival rates, (v) number of viable yeast cells in the lungs and spleen, (vi) splenic index, (vii) extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 38 publications
2
41
0
4
Order By: Relevance
“…isolates, they were less virulent than S. brasiliensis (Ss54, CBS 132990) isolate. In general, the virulence profiles of isolates obtained by CFU and survival assay S. luriei creating a well-supported clinical clade what is in agreement with De Beer et al 36 Various studies using animal models have shown differences in virulence among Sporothrix isolates, correlating the pigmentation of conidia, thermotolerance, 31 routes of infection 32 and origin 33,34 to the degree of virulence, nevertheless, none of these studies take into consideration the new taxonomy used for the clinical S. schenckii complex species. 11,12 In this study we did not find correlation between virulence profile of our isolates with thermotolerance or geographic origin (data obtained in our previously study 9 ) of them.…”
Section: 124142supporting
confidence: 70%
See 2 more Smart Citations
“…isolates, they were less virulent than S. brasiliensis (Ss54, CBS 132990) isolate. In general, the virulence profiles of isolates obtained by CFU and survival assay S. luriei creating a well-supported clinical clade what is in agreement with De Beer et al 36 Various studies using animal models have shown differences in virulence among Sporothrix isolates, correlating the pigmentation of conidia, thermotolerance, 31 routes of infection 32 and origin 33,34 to the degree of virulence, nevertheless, none of these studies take into consideration the new taxonomy used for the clinical S. schenckii complex species. 11,12 In this study we did not find correlation between virulence profile of our isolates with thermotolerance or geographic origin (data obtained in our previously study 9 ) of them.…”
Section: 124142supporting
confidence: 70%
“…35 Some comparative studies were conducted correlating the route of experimental infection 32 or clinical manifestation in humans with the virulence degree of different isolates. 33,34 Recently, Arrillaga-Moncrieff et al 2,3 showed different degrees of virulence among S. schenckii s. str., S. brasiliensis and S. globosa species.…”
Section: Characterization Of Virulence Profile Protein Secretion Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The virulence of S. schenckii is one of the factors thought to play a role in the development of sporotrichosis (32), but there are discordant results concerning disease evolution in experimental sporotrichosis with S. schenckii clinical isolates from cutaneous and disseminated infection (29,176), indicating that host immune responses also substantially participate in the progress of sporotrichosis (32).…”
Section: Immune Response In Sporotrichosismentioning
confidence: 99%
“…Other studies have reported similar results. Brito et al (29) studied the virulence of two strains of Sporothrix schenckii, isolated from patients with lymphocutaneous (group 1) or disseminated (group 2) sporotrichosis, by inoculating BALB/c mice. Comparison of the two groups revealed more severe disease in group 2 mice.…”
Section: Pathogenesis and Clinical Forms Human Diseasementioning
confidence: 99%